2016
DOI: 10.1093/bjsw/bcw134
|View full text |Cite
|
Sign up to set email alerts
|

Sexual Exploitation and Its Impact on Developing Sexualities and Sexual Relationships: The Need for Contextual Social Work Interventions

Abstract: This article considers how young people's developing sexualities are influenced by extra-familial social and cultural contexts, particularly in relation to experiences of sexual violence. It draws upon young people's voices to illustrate the choices they make when they encounter, or engage with, exploitative contexts. Utilising the cumulative evidence base of our studies into sexual exploitation, trafficking and violence over the past ten years, we employ Bourdieu's theory of the interplay between structure an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
33
0
1

Year Published

2018
2018
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 35 publications
(36 citation statements)
references
References 21 publications
0
33
0
1
Order By: Relevance
“…However, children may perceive their experience of sexual exploitation in very different terms to workers and policymakers. A child may think that they are in love with the perpetrator (Barnardo's, ), or a child who has been sexually abused since infancy may perceive abuse as normal (Firmin et al ., ). Such a child may attempt to gain some agency over the sexual abuse experience by making the exploiter pay.…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation
“…However, children may perceive their experience of sexual exploitation in very different terms to workers and policymakers. A child may think that they are in love with the perpetrator (Barnardo's, ), or a child who has been sexually abused since infancy may perceive abuse as normal (Firmin et al ., ). Such a child may attempt to gain some agency over the sexual abuse experience by making the exploiter pay.…”
Section: Discussionmentioning
confidence: 97%
“…In a study undertaken by Firmin et al . (), the authors explore how children's sexualities are influenced by sexual exploitation. They synthesised various findings from their previous work about children and sexual exploitation and found that children's sexualities can be skewed in different ways: through discourses that normalise abuse or blame the victim; or through structural inequalities whereby children are forced into exploitation in order to survive.…”
Section: Discussionmentioning
confidence: 99%
“…What we know about CSE has evolved over time and spans from the micro-to macrosystem of the ecological model. Initially, microsystem research on CSE explored the lived experiences of youth impacted by CSE [26][27][28]. Youth homelessness, which crosses multiple systems, ranges from the micro to the meso level because of the multiple factors that are influential.…”
Section: Discussionmentioning
confidence: 99%
“…An increased focus on opportunities also opens up new avenues to intervention, such as contextual safeguarding. 177 An approach to understanding and tackling harm outside the family, contextual safeguarding considers the immediate physical and social environments in which harm occurs and how places and practices might be modified to reduce risk and build resilience. Greater adoption of such approaches would help shift away from generic 'prevention' through one-size-fits-all awareness-raising or education at one end of the spectrum and prosecution at the other.…”
Section: Articulating Alternatives and Moving Towards Anti-racist Femmentioning
confidence: 99%